BUKU SAKU DESA SEBAGAI MEDIA PENGEMBANGAN POTENSI DESA KEDUNGDOWO DI SEKTOR EKONOMI DAN PARIWISATA - Masruro, Anisyah Aulia; Suksma, Cahaya (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2024)
Pocket books can be a medium for villages to develop and introduce the village's potential. The writing of the pocket book was carried out during the Pengabdian Berbasis Pemberdayaan Masyarakat Desa (PBPMD) which was held for 2 months, precisely on 5 June 2023 – 5 August 2023. The pocket book can be a source of accurate information because it contains all the data and information owned by the village.